PENGARUH CITRA MEREK TERHADAP KECINTAAN MEREK YANG DIMEDIASI OLEH SIKAP DAN KEPERCAYAAN (STUDI EMPIRIS PADA PRODUK SKINCARE RAMAH LINGKUNGAN) - Andira Ayu Pradisty; Soepatini Soepatini (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the influence of Green brand image on Green brand love by mediating the variables of Attitude toward the Green brand and Trust in the Green brand. The research uses a quantitative approach with a survey method involving 150 active students of Universitas Muhammadiyah Surakarta who have used The Body Shop products in the past three months. The data analysis technique employed is Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results show that Green brand image has a positive and significant direct effect on Green brand love. Additionally, a positive and significant indirect effect is also observed through the mediation of Attitude and Trust in the Green brand. The research model also demonstrates a good goodness of fit, with high R² and Q² values, indicating that the model is capable of significantly explaining the relationships between variables.